A novel integrated monitoring method for MPPF capacitor and IGBT junction temperature of half‐bridge modules - Wuyu Zhang; Lei Qi; Xiangyu Zhang; Bing Ji; Xiang Cui (IET Power Electronics, 2023)
Abstract Capacitance and Insulated gate bipolar transistor (IGBT) junction temperature are two critical healthy parameters for modular multilevel converters (MMC) sub‐modules (SMs) condition monitoring. This paper proposes an integrated monitoring method for capacitance degradation and IGBT junction temperature variation. By measuring multiple characteristics of the same port voltage, the capacitance and the junction temperature can be obtained simultaneously, which greatly simplifies the measurement unit required for condition evaluation and realizes the submodule‐level condition monitoring at a lower cost. The capacitance is characterized by voltage changes during capacitor discharging and the junction temperature is monitored by capacitor voltage overshoot (peak value) during IGBT turn‐off. Theoretical analysis and experimental results verify the effectiveness of the proposed method and articulated the influence of load current, SM capacitor pre‐discharge voltage, and junction temperature. Moreover, an online data‐acquisition circuit for time‐specific capacitor voltage characterization is devised.